La didáctica de las destrezas orales a través de las pronunciaciones figuradas: el francés en el método del Dr. Doppelheim - García Aranda, Mª Ángeles (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This paper is a contribution to the history of the materials used to teach French pronunciation to Spaniards, which addresses the articulatory descriptions and the notation system to represent the “pronunciaciones figuradas” that Pelayo Vizuete y Picón, under the pseudonym of Dr. Doppelheim, included in his manuals at the beginning of the 20th century
Keywords: pronunciation; French; doctor Doppelheim; Pelayo Vizuete y Picón; 20th century